A novel method of continuous cage‐side monitoring of hyperthyroid cats treated with radio‐iodine. (4th July 2015) - Roberts, E.; Gray, J. M.; Gunn, E.; Ramsey, I. K.
Abstract : A continuous monitoring system (MGP DM2000X) was assessed for monitoring γ radiation emissions and determining appropriate isolation times for hyperthyroid cats treated with radioactive iodine (I 131 ). Daily radiation emitted by 12 cats who had received a range of doses of I 131 (80–200 MBq) was measured and average background radiation readings deducted. The effective half‐lives of the I 131 in the cats were found to have a median of 2.54 days (range 1.40–3.24 days). Cats treated with 200 MBq emitted 5 µGy/day more exposure than cats treated with lower doses throughout the study period (P=0.032). All cats were found to emit a total radiation dose exposure less than 100 µGy (range 0–43 µGy) during days 18–21 of isolation. The potential additional dose exposure to owners was calculated at various days that might be considered for the cats to be returned to their owners. Using this provisional data, maximum isolation periods at this institution could be safely reduced to 17 days as long as certain precautions are followed. This preliminary study demonstrated that this novel cage‐side monitoring system can be used to calculate the effective half‐life of I 131 and to measure γ radiation exposure from treated cats, which may assist other institutions in determining appropriate isolation times for individual cats.